Beloved - Morrison, Toni. (London : Vintage, 2007)
Sethe, an escaped slave living in post-Civil War Ohio, struggles to keep Beloved, an intruder, from gaining possession of her present while throwing off the legacy of her past.
Adult
Keywords: African American women -- Fiction; Infanticide -- Fiction; Women slaves -- Fiction; African American women -- Fiction; Historical fiction; Infanticide -- Fiction; Slaves -- Fiction; Ohio -- Fiction; Ohio -- Fiction; Historical fiction